Big-five personality traits in P2P accommodation platforms: similar or different to hotel brands?. Issue 23 (2nd December 2021) - Wang, Xiaowei; Cheng, Mingming; Wong, IpKin Anthony; Teah, Min; Lee, Sean
ABSTRACT: This study uses an intrinsic lens to assess the brand personality of leading peer-to-peer (P2P) accommodation platforms and hotel brands through brand generated content. Using a word embedding technique, gaussian process model, and cosine similarity, fourteen brands' personality traits were analyzed and compared through brands' tweets. Findings reveal that P2P accommodation platforms have high scores in Conscientiousness, Extraversion, and Agreeableness, followed by Openness, but are lowest on Neuroticism. Contrary to popular assumption, brand personalities of P2P accommodation platforms are highly similar to traditional hotels. This study extended the current knowledge on P2P accommodation from a brand personality perspective. Methodologically, this study highlights the potential of social media to derive insights beyond the traditional survey approach to understand the human psychology and behavior of brands.